Outcome discrepancies and selective reporting: impacting the leading journals? - Padhraig S Fleming; Despina Koletsi; Kerry Dwan; Nikolaos Pandis (PLoS ONE, 2015)
Selective outcome reporting of either interesting or positive research findings is problematic, running the risk of poorly-informed treatment decisions. We aimed to assess the extent of outcome and other discrepancies and possible selective reporting between registry entries and published reports among leading medical journals.Randomized controlled trials published over a 6-month period from July to December 31st, 2013, were identified in five high impact medical journals: The Lancet, British Medical Journal, New England Journal of Medicine, Annals of Internal Medicine and Journal of American Medical Association were obtained. Discrepancies between published studies and registry entries were identified and related to factors including registration timing, source of funding and presence of statistically significant results.Over the 6-month period, 137 RCTs were found. Of these, 18% (n = 25) had discrepancies related to primary outcomes with the primary outcome changed in 15% (n = 20). Moreover, differences relating to non-primary outcomes were found in 64% (n = 87) with both omission of pre-specified non-primary outcomes (39%) and introduction of new non-primary outcomes (44%) common. No relationship between primary or non-primary outcome change and registration timing (prospective or retrospective; P = 0.11), source of funding (P = 0.92) and presence of statistically significant results (P = 0.92) was found.Discrepancies between registry entries and published articles for primary and non-primary outcomes were common among trials published in leading medical journals. Novel approaches are required to address this problem.